The level of scientific research skills of the biology students in the Philippines - Credo, Chillet G.; Embalsado, Justin Vianey M.; Madlambayan, Jed V.; Lim, Rich Paulo S.; Pineda, Maica S.; Salunga, Ricardo C.; Diego, Arnel A.; Credo, Tracy John A. (International Journal of Evaluation and Research in Education (IJERE), 2025)
Scientific research is essential in advancing human knowledge and in driving technological advancements. Students in the bachelor of science in biology program are expected to accomplish scientific research as a curriculum requirement. Possessing scientific research skills is essential for producing high-quality research outputs. A scale for assessing scientific research skills among senior high school students is available, however, there is an instrumentation gap in evaluating these skills at the tertiary level. In this regard, a research gap also exists in the assessment of students’ scientific research skills. Confirmatory factor analysis (CFA) using the JAMOVI software was utilized to establish the validity and reliability of the scientific research skill scale. The study included 133 officially enrolled biology students who voluntarily agreed to participate. The results provided compelling evidence that the tool effectively assesses scientific research skills in three key areas: scientific information development skills, scientific research management skills, and scientific research processing skills. This also affirmed the relevance of the three key areas in the biology program. The results also revealed that the level of scientific research skills of the students is on the average level across all three areas. This reflected an existing issue in the field of scientific research as mastery of skills is crucial in producing quality output, hence the study has significant implications for curriculum developers and policymakers of higher education institutions. There is a need to revisit the curriculum and to incorporate opportunities to enhance scientific research skills across various science subjects.